Genomic analyses of two novel biofilm-degrading methicillin-resistant Staphylococcus aureus phages - Khulood Hamid Dakheel; Raha Abdul Rahim; Vasantha Kumari Neela; Jameel R. Al-Obaidi; Tan Geok Hun; Mohd Noor Mat Isa; Khatijah Yusoff (BMC Microbiology, 2019)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) biofilm producers represent an important etiological agent of many chronic human infections. Antibiotics and host immune responses are largely ineffective against bacteria within biofilms. Alternative actions and novel antimicrobials should be considered. In this context, the use of phages to destroy MRSA biofilms presents an innovative alternative mechanism. Results Twenty-five MRSA biofilm producers were used as substrates to isolate MRSA-specific phages. Despite the difficulties in obtaining an isolate of this phage, two phages (UPMK_1 and UPMK_2) were isolated. Both phages varied in their ability to produce halos around their plaques, host infectivity, one-step growth curves, and electron microscopy features. Furthermore, both phages demonstrated antagonistic infectivity on planktonic cultures. This was validated in an in vitro static biofilm assay (in microtiter-plates), followed by the visualization of the biofilm architecture in situ via confocal laser scanning microscopy before and after phage infection, and further supported by phages genome analysis. The UPMK_1 genome comprised 152,788 bp coding for 155 putative open reading frames (ORFs), and its genome characteristics were between the Myoviridae and Siphoviridae family, though the morphological features confined it more to the Siphoviridae family. The UPMK_2 has 40,955 bp with 62 putative ORFs; morphologically, it presented the features of the Podoviridae though its genome did not show similarity with any of the S. aureus in the Podoviridae family. Both phages possess lytic enzymes that were associated with a high ability to degrade biofilms as shown in the microtiter plate and CLSM analyses. Conclusions The present work addressed the possibility of using phages as potential biocontrol agents for biofilm-producing MRSA.